The impact of the level of health services on the satisfaction of resident women who benefit from obstetric services- A field study at Slimane Amirat Specialized Hospital for Gynecology and Obstetrics in M’sila - Safari, Sabah; Khelil, Naziha (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2025)
This study aims to examine the impact of the level of healthcare services, on the satisfaction of resident women, who benefit from maternity services at the specialized obstetrics and gynecology hospital'' Slimane Amirat'' in M’sila. The study focuses on three main dimensions: tangibility (equipment and infrastructure), responsiveness (speed of service and efficiency in handling cases), and empathy (psychological care and human interaction). The study seeks to improve healthcare service quality to align with the needs and expectations of resident women, thereby achieving their satisfaction and ensuring their continued loyalty to the institution a factor that positively impacts public health. The study employed a descriptive approach in the theoretical part to establish core concepts, and an analytical approach in the fieldwork, where a questionnaire was distributed to a sample of 49 women who received maternity services at the hospital. Data were analyzed using SPSS V27 to assess relationships between variables and draw conclusions. The study found that: . There is a statistically significant impact of responsiveness on the satisfaction of resident women benefiting from maternity services at the hospital (α ≤ 0.05). . There is a statistically significant impact of tangibility on the satisfaction of resident women benefiting from maternity services at the hospital (α ≤ 0.05). . There is no statistically significant impact of empathy on the satisfaction of resident women benefiting from maternity services at the hospital (α ≤ 0.05).